First and Second Language Acquisition in Children: Socio-cognitive Approach (Sastra Inggris UNPAM, 2024)
Humans carry out social interactions through communication, and such communication with language, as human children, begin to recognize communication from the process of thinking and it is called cognitive. Concerning language acquisition in children, children’s communicative and interactive abilities implicitly (through eye gaze), and explicitly (through the choice of objects) become a problem when influential factors cognize children’s language with surrounding influences, in addition to understanding the perspectives of others and surroundings, thus contributing to social interaction. The purpose of this study is to obtain information on opportunities and participation in children’s language acquisition through the exploration of language effect elements of children’s alignment cognition with influential factors by semiotics and sociolinguistics through synchronized socio-cognitive alignment and in factors that become supporting factors for children’s first language and second language acquisition, both in environmental involvement and socially and communicatively, with descriptive qualitative research methods through observation and semi-structured interviews by analyzing through audio video shoots in class, including instructions, language, intonation, gestures, eye gaze, and proxemics, it appears that the opportunity for involvement in coherence, namely the alignment of semiotic resources, is found to be very influential on the acquisition of children’s first and second languages by the previous factors. Thus, the synchronization of semiotic resources is expressed through children’s cognitive alignment.